Evolving Commitments: A Comparative Analysis of Nepal’s Nationally Determined Contributions under the Paris Agreement - Thakuri, Sudeep; Pokharel, Gobinda Prasad; KC, Deepak (Tribhuvan University Journal, 2025)
Nepal first submitted its Intended Nationally Determined Contributions (INDC) in 2016 under the Paris Agreement (PA) of the United Nations Framework Convention on Climate Change (UNFCCC). Nationally Determined Contributions (NDCs) are climate action plans that a country commits to at the international level to address climate change. The implementation of country’s NDCs and the achievement of its goals are growing concerns among policymakers and negotiators. We review and analyze Nepal’s NDCs trajectory by comparing four key submissions: the INDC (February 11, 2016), the first NDC (October 5, 2016), second NDC (December 8, 2020) and the NDC3.0 (May 19, 2025). A systematic comparative analysis of the NDCs of Nepal shows a progressive increase in its ambition, sectoral coverage, quantification of mitigation targets, integrating adaptation strategies, stakeholder involvement, budget size, and transparency, but challenges remain in terms of its implementation capacity, financing, and long-term sustainability. This article provides a summary into Nepal’s climate commitments for policymakers, researchers, and practitioners.